Celiac Disease in Patients With Type 1 Diabetes: Screening and Diagnostic Practices. (July 2013) - Simpson, Suzanne M.; Ciaccio, Edward J.; Case, Shelley; Jaffe, Nancee; Mahadov, Srihari; Lebwohl, Benjamin; Green, Peter H.
Objective: The purpose of this study was to investigate screening practices for celiac disease in patients with type 1 diabetes across North America. The research question investigated was whether diabetes centers screen for celiac disease in type 1 diabetes more frequently than other facilities. Research Design and Methods: A survey with 27 questions on screening practices for celiac disease in patients with type 1 diabetes was designed by experts in celiac disease and diabetes. Surveys were sent by email to diabetes educators and dietitians throughout the United States and Canada between December 2010 and May 2011. Results: There were 514 respondents from 484 endocrine clinics, diabetes clinics, private practices, community nutrition centers, and inpatient centers. Thirty-five percent of work locations screened for celiac disease, with endocrine clinics reporting screening at the highest frequency (80%). Tissue transglutaminase was the most common screening test used. The most frequently recommended treatment of confirmed celiac disease was a gluten-free diet. However, only 71% of respondents recommended biopsy in patients with positive serologies. Most respondents (55.3%) reported that the gluten-free diet resulted in symptom improvement in the majority of patients. Conclusions: Staff at endocrine clinics were more likely to suggest screening for celiac disease in patients with type 1 diabetes. Both low screening frequency as well as inconsistency in management of positive celiac disease serological tests indicated an increase in education regarding celiac disease in patients with type 1 diabetes is required. In addition uniform guidelines should be developed.